Polymer composite emulsion, preparation method thereof and preparation method of lithium ion battery separator
Through the preparation method of polymer composite emulsion, the lack of thermal stability and adhesive strength of lithium-ion battery separators is solved, and the efficient preparation of battery separators and excellent electrochemical properties are achieved.
Patent Information
- Application Number
- CN202411075630.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-07
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-08-07
AI Technical Summary
The existing lithium-ion battery separators have shortcomings in thermal stability and bonding strength, and the preparation process consumes time and energy, and are prone to stratification, which affects the safety and energy density of the battery.
The preparation method of polymer composite emulsion is adopted, and the oil-phase solution and the aqueous solution are mixed through the mixing and shock steps to form a Pickering emulsion, and the polymer composite emulsion is obtained through nitrogen-discharge and heating polymerization steps. A coating that is closely bonded to the positive and negative electrode sheet of the battery is only required for a single coating.
The tight adhesion of polymer composite emulsion and the base film is achieved, the thermal stability and structural strength of the separator are improved, the safety risks of the battery in extreme environments are reduced, and the operational efficiency of the battery is improved.
Smart Images

Figure CN118955794B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a coating material, in particular to a coating material coated on a battery separator. Background Art
[0002] The internal structure of a lithium-ion battery mainly includes: a positive electrode, a negative electrode, an electrolyte, and a separator. The separator is set between the positive electrode and the negative electrode to prevent the two from contacting each other and causing a short circuit. In order to ensure the electrochemical performance of the lithium-ion battery, the separator must be wetted by the electrolyte and transfer lithium ions to achieve battery charging and discharging. Specifically, the performance of the separator has an important impact on the electrical performance, safety performance, and cycle performance of the battery.
[0003] The main diaphragms used in the industry at present include: polyolefin microporous diaphragms, which have poor wettability to electrolytes and low thermal stability; ceramic wet-coated polyethylene diaphragms. Although the application of ceramic coating can improve the puncture resistance of the diaphragm, the ceramic coating will also lead to a thicker diaphragm, which in turn affects the energy density of the battery, and the diaphragm has a low rupture temperature. When the battery is operated for a long time, its safety performance is unstable; organic wet-coated polyethylene diaphragms, which need to be hot-pressed with the electrode, so the preparation process has strict requirements and high energy consumption; high-performance diaphragms, in order to ensure the thermal stability of the diaphragm, it is necessary to sequentially form multiple layers of coating on the base film, wherein the materials used in each coating are different and they must be prepared separately, so the process is time-consuming and energy-intensive, and since there is no chemical force between the coatings, the layers are prone to stratification after being placed for a period of time, and the thickness of the diaphragm fluctuates, affecting the performance of the diaphragm.
[0004] In view of the above-mentioned problems, it is necessary to provide a slurry that can form a coating with high bonding strength to the positive and negative electrodes of the battery and excellent thermal stability with only a single coating. Summary of the invention
[0005] The object of the present invention is to provide a slurry which can form a coating with high bonding strength to positive and negative electrode sheets of a battery and excellent thermal stability by only a single coating.
[0006] To achieve the above-mentioned purpose, the present invention provides a method for preparing a polymer composite emulsion, comprising: a mixing and shaking step, mixing an oil phase solution with an aqueous phase solution to obtain an oil-water mixed liquid, and subjecting the oil-water mixed liquid to ultrasonic shaking to obtain a Pickering emulsion, wherein: the oil phase solution comprises: one or more of a plant oil-based epoxy ring-opening monomer, a styrene monomer, an acrylamide monomer, a vinyl acetate monomer, and an acrylonitrile monomer; and the aqueous phase solution comprises: an aramid fiber suspension; and a polymerization step, nitrogen-deoxygenating the Pickering emulsion, and adding a water-soluble initiator to obtain a Pickering mixed liquid, and then heating the Pickering mixed liquid for polymerization to obtain a polymer composite emulsion.
[0007] More preferably, the method further comprises: a filtering step of cooling the polymer composite emulsion to room temperature and filtering it with a filter screen of 100 to 300 meshes.
[0008] More preferably, in the mixing and shaking step, the oil phase solution and the water phase solution are mixed in a weight ratio of 1:4 to 8 to obtain the oil-water mixed solution.
[0009] More preferably, in the mixing and shaking step, the oil-water mixture is shaken with ultrasonic energy of 600 to 800 W for 10 to 15 minutes.
[0010] More preferably, in the mixing and shaking step, the vegetable oil-based epoxy ring-opening monomer, styrene monomer, acrylamide monomer, vinyl acetate monomer, and acrylonitrile monomer are sequentially added dropwise to the aqueous phase solution to obtain the oil-water mixed solution.
[0011] More preferably, in the mixing and shaking step, the oil phase solution comprises: one or more of 10 to 40 parts by weight of a vegetable oil-based epoxy ring-opening monomer, 1 to 10 parts by weight of a styrene monomer, 2 to 5 parts by weight of an acrylamide monomer, 3 to 10 parts by weight of a vinyl acetate monomer, and 1 to 8 parts by weight of an acrylonitrile monomer; and the water phase solution comprises: 100 to 500 parts by weight of an aramid fiber suspension.
[0012] More preferably, in the polymerization step, the time for deoxygenation by nitrogen is 0.5 to 1 hr.
[0013] More preferably, in the polymerization step, the Pickering mixed solution comprises 50 to 150 parts by weight of the Pickering emulsion and 0.3 to 0.8 parts by weight of one or more of the water-soluble initiators.
[0014] More preferably, in the polymerization step, the Pickering mixed solution is polymerized at a temperature of 60 to 80° C. for 3 to 6 hours.
[0015] More preferably, in the polymerization step, the aqueous initiator comprises one or more of ammonium persulfate, potassium persulfate, and metal salts of peroxides.
[0016] More preferably, the preparation method of the vegetable oil-based epoxy ring-opening monomer comprises: (S1A) mixing 10 to 40 parts by weight of vegetable oil, 1 to 6 parts by weight of N-methylethanolamine, and 0.1 to 2 parts by weight of a catalyst, and sealing and heating to 50 to 80° C., reacting for 8 hours, and then removing the unreacted product and the catalyst to obtain a vegetable oil-based precursor; (S2A) mixing 10 to 40 parts by weight of a vegetable oil-based precursor and 4 to 25 parts by weight of an acid anhydride, and sealing and heating to 60 to 80° C., reacting for 8 to 12 hours, and then removing the unreacted product. (S3A) mixing 10 to 40 parts by weight of a vegetable oil-based acrylate monomer, 3 to 10 parts by weight of perbenzoic acid, and 5 to 15 parts by weight of sodium carbonate, and stirring them in a sealed container at room temperature for 12 hours, and then removing the unreacted substances to obtain a vegetable oil-based epoxy monomer; and (S4A) mixing 10 to 40 parts by weight of a vegetable oil-based epoxy monomer and 3 to 10 parts by weight of perchloric acid, and reacting them at room temperature for 12 to 24 hours, and then removing the unreacted substances to obtain a vegetable oil-based epoxy ring-opening monomer.
[0017] More preferably, the method for preparing the aramid fiber suspension comprises: (S1B) dissolving 5 to 30 parts by weight of sodium hydroxide in 100 to 500 parts by weight of deionized water to obtain a sodium hydroxide solution; (S2B) mixing 5 to 30 parts by weight of polyterephthalamide fiber, 1000 to 2000 parts by weight of DMSO, and the sodium hydroxide solution, and stirring them for 6 to 12 hours to obtain a uniform solution; (S3B) subjecting the uniform solution to high-speed shaking and vacuum filtration to obtain an aramid fiber precipitate; (S4B) washing the aramid fiber precipitate with saturated sodium chloride to obtain an aramid fiber purified product; and (S5B) diluting the aramid fiber purified product with deionized water to obtain an aramid fiber suspension.
[0018] More preferably, the vegetable oil comprises one or more of sunflower oil, Chinese tallow tree oil, olive oil, linseed oil, rubber seed oil, castor oil, tung oil, and palm oil; or the catalyst comprises one or more of sodium hydroxide, potassium hydroxide, and sodium methoxide.
[0019] The present invention further provides a polymer composite emulsion, which is prepared by the method described above, wherein the polymer composite emulsion contains polymer composite microspheres, and the polymer composite microspheres contain: a core, whose composition raw materials include: polystyrene; a first shell layer, which is coated on the outer edge of the core, and whose composition raw materials include: polyacrylonitrile; a second shell layer, which is coated on the outer edge of the first shell layer, and whose composition raw materials include: polyvinyl acetate; a third shell layer, which is coated on the outer edge of the second shell layer, and whose composition raw materials include: plant oil polymer; and aramid fiber, which is arranged on the outer edge of the third shell layer.
[0020] More preferably, the polymer composite microspheres comprise, based on the total weight of the polymer composite microspheres, one or more of: A weight parts of aramid fiber, B weight parts of vegetable oil polymer, C weight parts of polyacrylamide, D weight parts of polyvinyl acetate, E weight parts of polystyrene, and F weight parts of polyacrylonitrile, wherein: A is 0.1 to 2, B is 20 to 40, C is 10 to 20, D is 5 to 25, E is 4.9 to 23, F is 5 to 10, and A+B+C+D+E+F=100.
[0021] The present invention further provides a method for preparing a lithium-ion battery separator, comprising: applying the polymer composite emulsion described above to one or both sides of a base film to obtain a composite separator; and drying the composite separator at a temperature of 50 to 70° C. for 0.5 to 2 minutes to obtain the lithium-ion battery separator.
[0022] The effectiveness of the present invention over the prior art is that the present invention uses vegetable oil as the main raw material of the oil phase solution, so its preparation process is more environmentally friendly, and because the polymer composite emulsion has good wettability, it only needs to be coated on the base film once and dried to be tightly bonded to the base film, and effectively improve the thermal stability and structural strength of the base film, so that when the internal temperature of the battery changes greatly, the deformation of the diaphragm in the TD direction or MD direction is small, and because the rupture temperature of the diaphragm can be effectively increased, the safety and stability of the battery can be guaranteed when it is operated in extreme environments for a long time, and the operating efficiency of the battery is improved.
[0023] In addition, the present invention uses polyterephthalamide fiber as the raw material of the aqueous solution, and deprotonates and dissociates it to obtain a stable aramid fiber suspension; and uses vegetable oil as the raw material of the oil phase solution to synthesize and prepare a vegetable oil-based epoxy ring-opening monomer, and adds a certain proportion of acrylamide, styrene, vinyl acetate, and acrylonitrile monomers during the polymerization process, and then uses the aramid fiber suspension as a stabilizer to perform a polymerization step to obtain a polymer composite emulsion, wherein: the preparation method of the present invention is more environmentally friendly and energy-saving, and the polymer composite microspheres contained in the polymer composite emulsion form a stable core-shell structure, and the polymer composite microspheres have an interaction force, so that the polymer composite emulsion and the base membrane have high stability, which can avoid the thickness of the diaphragm changing or forming a stratification phenomenon when placed for a long time, thereby reducing the risk of the diaphragm in the production process, and the obtained diaphragm has strong adhesion to the pole piece and has a wide temperature processing window. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is a flow chart for illustrating a method for preparing a polymer composite emulsion;
[0025] Figure 2 is a flow chart for illustrating a method for preparing a polymer composite emulsion;
[0026] Figure 3 is a flow chart for illustrating a method for preparing a vegetable oil-based epoxy ring-opening monomer;
[0027] Figure 4 is a flow chart for illustrating a method for preparing an aramid fiber suspension;
[0028] Figure 5 is a structural diagram to illustrate the structural characteristics of polymer composite microspheres;
[0029] Figure 6 It is a partial enlarged view, used to illustrate the implementation mode of connecting the polymer composite microspheres with the basement membrane. DETAILED DESCRIPTION
[0030] In order to make the above and / or other purposes, effects, and features of the present invention more clearly understood, preferred embodiments are specifically described below in detail:
[0031] One object of the present invention is to provide a method for preparing a polymer composite emulsion, such as Figure 1As shown, it includes: a mixing and shaking step 1, mixing an oil phase solution with an aqueous phase solution to obtain an oil-water mixture, and ultrasonically shaking the oil-water mixture to obtain a Pickering emulsion, wherein: the oil phase solution includes: one or more of plant oil-based epoxy ring-opening monomers, styrene monomers, acrylamide monomers, vinyl acetate monomers, and acrylonitrile monomers, but not limited thereto; and the aqueous phase solution includes: an aramid fiber suspension; and a polymerization step 2, nitrogen-deoxygenating the Pickering emulsion, and adding a water-soluble initiator to obtain a Pickering mixture, and then heating the Pickering mixture for polymerization to obtain a polymer composite emulsion. In a preferred embodiment, in order to remove the agglomerated or agglomerated parts of the polymer composite emulsion so that it can be evenly and evenly coated on the battery base membrane, and the surface will not be uneven after drying, such as Figure 2 As shown, it further comprises: a filtering step 3, which is to cool the polymer composite emulsion to room temperature and filter it with a filter screen of 100 to 300 meshes. In another preferred embodiment, the filter screen is made of nylon, but not limited thereto.
[0032] More preferably, in order to ensure the structural strength, adhesion, heat resistance and thermal shrinkage of the polymer composite emulsion, it is compounded with a base film, and when used as a separator of a lithium-ion battery, the safety and electrochemical performance of the battery operation can be ensured, wherein: in the mixing and shaking step 1, the oil phase solution and the water phase solution are mixed in a weight ratio of 1:4 to 8 to obtain the oil-water mixture; or in the mixing and shaking step 1, the oil-water mixture is shaken with an ultrasonic energy of 600 to 800 W for 10 to 15 minutes; or in the mixing and shaking step 1, a vegetable oil-based epoxy ring-opening monomer, a styrene monomer, an acrylamide monomer, a vinyl acetate monomer, and an acrylonitrile monomer are sequentially added dropwise to the water phase solution to obtain the oil-water mixture; or in the mixing and shaking step 1, the oil phase solution contains: 10 to 40 parts by weight of a vegetable oil-based epoxy ring-opening monomer, 1 to 10 parts by weight of styrene monomer, 2 to 5 parts by weight of acrylamide monomer, 3 to 10 parts by weight of vinyl acetate monomer, and 1 to 8 parts by weight of acrylonitrile monomer, but not limited thereto; and the aqueous phase solution comprises: 100 to 500 parts by weight of aramid fiber suspension; or in the polymerization step 2, the nitrogen deoxygenation time is 0.5 to 1 hour; or in the polymerization step 2, the Pickering mixture comprises 50 to 150 parts by weight of the Pickering emulsion, and 0.3 to 0.8 parts by weight of one or more of the water-soluble initiators, but not limited thereto; or in the polymerization step 2, the Pickering mixture is polymerized at a temperature of 60 to 80° C. for 3 to 6 hours; or in the polymerization step 2, the aqueous initiator comprises: one or more of ammonium persulfate, potassium persulfate, and a metal salt of a peroxide, but not limited thereto.
[0033] Better, if Figure 3As shown, the preparation method of the vegetable oil-based epoxy ring-opening monomer comprises: (S1A) mixing 10 to 40 parts by weight of vegetable oil, 1 to 6 parts by weight of N-methylethanolamine, and 0.1 to 2 parts by weight of a catalyst, and sealing and heating to 50 to 80° C., reacting for 8 hours, and then removing the unreacted product and the catalyst to obtain a vegetable oil-based precursor; (S2A) mixing 10 to 40 parts by weight of a vegetable oil-based precursor and 4 to 25 parts by weight of an acid anhydride, and sealing and heating to 60 to 80° C., reacting for 8 to 12 hours, and then removing the unreacted product. (S3A) mixing 10 to 40 parts by weight of a plant oil-based acrylate monomer, 3 to 10 parts by weight of perbenzoic acid, and 5 to 15 parts by weight of sodium carbonate, and stirring them in a sealed container for 12 hours at room temperature, and then removing the unreacted substances, to obtain a plant oil-based epoxy monomer; and (S4A) mixing 10 to 40 parts by weight of a plant oil-based epoxy monomer and 3 to 10 parts by weight of perchloric acid, reacting them at room temperature for 12 to 24 hours, and then removing the unreacted substances, to obtain a plant oil-based epoxy ring-opening monomer. In a preferred embodiment, the plant oil comprises one or more of sunflower seed oil, Chinese tallow tree oil, olive oil, linseed oil, rubber seed oil, castor oil, tung oil, and palm oil, but not limited thereto; or the catalyst comprises one or more of sodium hydroxide, potassium hydroxide, and sodium methoxide, but not limited thereto.
[0034] Another embodiment of the method for preparing a vegetable oil-based epoxy ring-opening monomer is provided below, wherein the prepared vegetable oil-based epoxy ring-opening monomer is a linseed oil-based epoxy ring-opening monomer.
[0035] (1) First, 50 parts by weight of linseed oil are weighed and purged with nitrogen at 100° C. for 30 minutes, and then cooled to 65° C. Next, the linseed oil is mixed with 8 parts by weight of N-methylethanolamine and 1 part by weight of sodium methoxide solution (5 mol / L), and the mixture is sealed and reacted at 65° C. for 8 hours to obtain a first mixed solution. Next, the first mixed solution is dissolved in 60 parts by weight of dichloromethane (DCM) to obtain a second mixed solution, and the second mixed solution is washed with saturated sodium chloride and then dried with anhydrous magnesium sulfate to obtain a plant oil-based precursor.
[0036] (2) Next: 50 parts by weight of a plant oil-based precursor, 15 parts by weight of anhydride, and 0.4 parts by weight of 4-dimethylaminopyridine were mixed, and the mixture was sealed and reacted at 65° C. for 8 hours to obtain a third mixed solution; then, the third mixed solution was dissolved in 60 parts by weight of dichloromethane (DCM) to obtain a fourth mixed solution, and then the fourth mixed solution was washed with saturated sodium bicarbonate and saturated sodium chloride, respectively, and then dried with anhydrous magnesium sulfate, and then passed through an alkaline alumina column to obtain a plant oil-based acrylate monomer.
[0037] (3) Then: 50 parts by weight of the vegetable oil-based acrylate monomer was dissolved in 100 parts by weight of dichloromethane (DCM), followed by the addition of 20 parts by weight of perbenzoic acid and 10 parts by weight of sodium carbonate, and stirred at room temperature for 8 hours, and then washed with saturated sodium thiosulfate, saturated sodium bicarbonate, and saturated sodium chloride, respectively, and then dried with anhydrous magnesium sulfate, and then passed through an alkaline alumina column to obtain a vegetable oil-based epoxy monomer.
[0038] (4) Next, 50 parts by weight of a vegetable oil-based epoxy monomer was dissolved in 200 parts by weight of tetrahydrofuran to obtain Agent A; 10 parts by weight of perchloric acid was dissolved in 200 parts by weight of water to obtain Agent B; then, Agent A and Agent B were mixed and stirred for 30 hours, and then washed with saturated sodium thiosulfate, saturated sodium bicarbonate, and saturated sodium chloride, respectively, and then dried with anhydrous magnesium sulfate, and then passed through an alkaline alumina column to obtain a linseed oil-based epoxy ring-opening monomer.
[0039] Better, if Figure 4 As shown, the preparation method of the aramid fiber suspension includes: (S1B) dissolving 5 to 30 parts by weight of sodium hydroxide in 100 to 500 parts by weight of deionized water to obtain a sodium hydroxide solution; (S2B) mixing 5 to 30 parts by weight of polyterephthalamide fiber, 1000 to 2000 parts by weight of DMSO, and the sodium hydroxide solution, and stirring them for 6 to 12 hours to obtain a uniform solution; (S3B) subjecting the uniform solution to high-speed shaking and vacuum filtration to obtain an aramid fiber precipitate; (S4B) washing the aramid fiber precipitate with saturated sodium chloride to obtain an aramid fiber purified product; and (S5B) diluting the aramid fiber purified product with deionized water to obtain an aramid fiber suspension.
[0040] Another embodiment of the method for preparing an aramid fiber suspension is provided below: 10 g of sodium hydroxide is dissolved in 150 ml of deionized water to obtain a sodium hydroxide solution; 5 g of polyterephthalamide fiber, 1000 ml of dimethyl sulfoxide (DMSO), and the sodium hydroxide solution are stirred and mixed for 8 hours to obtain a uniform solution; the uniform solution is then subjected to high-speed oscillation and vacuum filtration to obtain an aramid fiber precipitate; the aramid fiber precipitate is then repeatedly washed with saturated sodium chloride to purify and separate the aramid fiber and obtain a purified aramid fiber product; and the purified aramid fiber product is then diluted with deionized water to obtain a uniform aramid fiber suspension.
[0041] The present invention further provides a polymer composite emulsion, which is prepared by the above method, such as Figure 5As shown, the polymer composite emulsion contains polymer composite microspheres, and the polymer composite microspheres include: a core 4, whose constituent materials include: polystyrene; a first shell layer 5, which is coated on the outer edge of the core 4, and whose constituent materials include: polyacrylonitrile; a second shell layer 6, which is coated on the outer edge of the first shell layer 5, and whose constituent materials include: polyvinyl acetate; a third shell layer 7, which is coated on the outer edge of the second shell layer 6, and whose constituent materials include: vegetable oil polymer; and aramid fiber 8, which is arranged on the outer edge of the third shell layer 7. In a preferred embodiment, based on the total weight of the polymer composite microsphere, it comprises: one or more of A weight parts of aramid fiber 8, B weight parts of vegetable oil polymer, C weight parts of polyacrylamide, D weight parts of polyvinyl acetate, E weight parts of polystyrene, and F weight parts of polyacrylonitrile, but not limited thereto, wherein: A is 0.1 to 2, B is 20 to 40, C is 10 to 20, D is 5 to 25, E is 4.9 to 23, F is 5 to 10, and A+B+C+D+E+F=100. In another preferred embodiment, based on the total weight of the polymer composite emulsion, it comprises: one or more of 0.1 to 2wt% of aramid fiber 8, 20 to 40wt% of vegetable oil polymer, 10 to 20wt% of polyacrylamide, 5 to 25wt% of polyvinyl acetate, 4.9 to 23wt% of polystyrene, and 5 to 10wt% of polyacrylonitrile, but not limited thereto. In another preferred embodiment, the solid content of the aramid fiber 8 is 0.1 wt % to 1 wt %, but not limited thereto. Specifically, as shown in the above paragraphs, the weight parts described in the specification of the present invention can be converted into weight percentages.
[0042] The present invention further provides a method for preparing a lithium-ion battery separator, comprising: applying the polymer composite emulsion prepared above to one or both sides of a base film to obtain a composite separator; and drying the composite separator at a temperature of 50 to 70° C. for 0.5 to 2 minutes to obtain the lithium-ion battery separator. Figure 6 The figure shows an implementation mode of coating the polymer composite emulsion onto the base film.
[0043] The following is a method for preparing the lithium-ion battery separator of Example 1.
[0044] (S101) 15 parts by weight of linseed oil-based epoxy ring-opening monomer, 5 parts by weight of styrene monomer, 4 parts by weight of acrylonitrile monomer, 5 parts by weight of vinyl acetate monomer, and 6 parts by weight of acrylamide monomer are mixed to obtain an oil phase solution, and the oil phase solution is added dropwise to 140 parts by weight of an aramid fiber suspension (aqueous phase solution) having a solid content of 0.5 wt% to obtain an oil-water mixture, and then the oil-water mixture is treated with an ultrasonic crusher at a power of 600 W for 15 minutes to obtain a Pickering emulsion, wherein the stability, particle size and viscosity of the Pickering emulsion are summarized in the following Table 1.
[0045] (S102) 30 parts by weight of the pickering emulsion is subjected to nitrogen deoxygenation at 65° C. for 30 minutes in a constant temperature device, and then 0.1 parts by weight of ammonium persulfate is added to react for 3 hours to obtain a pickering mixed solution. The temperature of the constant temperature device is then increased to 80° C., and the pickering mixed solution is reacted for 30 minutes. The temperature is then lowered to room temperature, and the filter residue is removed with a 150-mesh nylon filter to obtain a polymer composite emulsion.
[0046] (S103) 5 parts by weight of the polymer composite emulsion is evenly coated on the PE base film using a small roller coater in the laboratory, and baked in an oven at 60°C for 1 minute to obtain the lithium ion battery separator of Example 1.
[0047] The following is a method for preparing a lithium-ion battery separator according to Comparative Example 1.
[0048] The difference between Comparative Example 1 and Example 1 is that: in step (S101), the solid content of the aramid fiber suspension is 0.2wt%; and in step (S103), the baking time is 2 minutes, and the remaining process steps and parameter conditions are the same as those in Example 1, so they are not described in detail here. In addition, the stability, particle size and viscosity of the Pickering emulsion of Comparative Example 1 are summarized in the following Table 1. Compared with Example 1, in step (S101), the solid content of the aramid fiber suspension in Comparative Example 1 is too low, resulting in poor stability of the prepared Pickering emulsion, and after the Pickering emulsion is dried on the PE base film and forms a Pickering coating, the bonding strength between the Pickering coating and the PE base film is greatly reduced, resulting in the risk of stratification between the two, and resulting in a decrease in the thermal stability of the lithium-ion battery separator. In addition, the baking time in step (S103) of comparative example 1 is too long, which causes the outer layer of the Pickering coating to melt and affects the consistency of the overall thickness of the lithium-ion battery separator, making it more likely to cause delamination.
[0049] The following is a method for preparing a lithium-ion battery separator according to Comparative Example 2.
[0050] The difference between Comparative Example 2 and Example 1 is that: in step (S101), the content of the aramid fiber suspension is 280 parts by weight; and in step (S103), the baking time is 2 minutes, and the remaining process steps and parameter conditions are the same as those in Example 1, so they are not described in detail here. In addition, the stability, particle size and viscosity of the Pickering emulsion of Comparative Example 2 are summarized in the following Table 1. Among them, in Comparative Example 2, compared with Example 1, the weight of the aramid fiber suspension in step (S101) is too high, resulting in agglomeration of the prepared Pickering emulsion, and it cannot be evenly and densely coated on the PE base film, and the bonding strength between the Pickering coating and the PE base film is greatly reduced; and the internal resistance of the lithium-ion battery separator is greatly increased, which affects the charge and discharge performance of the lithium-ion battery and creates a safety hazard. In addition, the baking time in step (S103) of Comparative Example 2 is too long, which causes the outer layer of the Pickering coating to melt and affects the consistency of the overall thickness of the lithium-ion battery separator, making it more likely to cause delamination.
[0051] Table 1. Performance of Pickering emulsion and modified diaphragm in various examples and comparative examples
[0052]
[0053] Compared with the prior art, the present invention has the following advantages: the present invention uses vegetable oil as the main raw material of the oil phase solution, so its preparation process is more environmentally friendly, and because the polymer composite emulsion has good wettability, it only needs to be coated on the base film once and dried to be tightly bonded to the base film, and the subsequent bonding strength with the positive and negative electrodes is high, and the thermal stability and structural strength of the base film are effectively improved, so that when the internal temperature of the battery changes greatly, the deformation of the diaphragm in the TD direction or MD direction is small, and because the rupture temperature of the diaphragm can be effectively increased, the safety and stability of the battery can be guaranteed when it is operated in extreme environments for a long time, and the operating efficiency of the battery is improved.
[0054] In addition, the present invention uses polyterephthalamide fiber as the raw material of the aqueous solution, and deprotonates and dissociates it to obtain a stable aramid fiber suspension; and uses vegetable oil as the raw material of the oil phase solution to synthesize and prepare a vegetable oil-based epoxy ring-opening monomer, and adds a certain proportion of acrylamide, styrene, vinyl acetate, and acrylonitrile monomers during the polymerization process, and then uses the aramid fiber suspension as a stabilizer to perform a polymerization step to obtain a polymer composite emulsion, wherein: the preparation method of the present invention is more environmentally friendly and energy-saving, and the polymer composite microspheres contained in the polymer composite emulsion form a stable core-shell structure, and the polymer composite microspheres have an interaction force, so that the polymer composite emulsion and the base membrane have high stability, which can avoid the thickness of the diaphragm changing or forming a stratification phenomenon when placed for a long time, thereby reducing the risk of the diaphragm in the production process, and the obtained diaphragm has strong adhesion to the pole piece and has a wide temperature processing window.
[0055] However, what is described above is only a preferred embodiment of the present invention, but it cannot be used to limit the patent protection scope of the present invention; therefore, all simple equivalent changes and modifications made according to the patent protection scope of the present invention and the contents of the specification still fall within the patent protection scope of the present invention.
Claims
1. A method for preparing a polymer composite emulsion, comprising: A mixing and shaking step, mixing an oil phase solution with an aqueous phase solution to obtain an oil-water mixture, and subjecting the oil-water mixture to ultrasonic shaking to obtain a Pickering emulsion, wherein: The oil phase solution comprises: one or more of a plant oil-based epoxy ring-opening monomer, a styrene monomer, an acrylamide monomer, a vinyl acetate monomer, and an acrylonitrile monomer; and The aqueous phase solution comprises: 100 to 140 parts by weight of an aramid fiber suspension having a solid content of 0.5 wt %; and In a polymerization step, the Pickering emulsion is deoxygenated by nitrogen, and a water-soluble initiator is added to obtain a Pickering mixed solution, and the Pickering mixed solution is then heated for polymerization to obtain a polymer composite emulsion.
2. The method according to claim 1 further comprises: a filtering step, wherein the polymer composite emulsion is cooled to room temperature and filtered through a filter screen with a mesh size of 100 to 300.
3. The method according to claim 1, wherein: In the mixing and shaking step, the oil phase solution and the water phase solution are mixed in a weight ratio of 1:4 to 8 to obtain the oil-water mixed solution.
4. The method according to claim 1, wherein: In the mixing and shaking step, the oil-water mixture is shaken with ultrasonic energy of 600 to 800 W for 10 to 15 minutes.
5. The method according to claim 1, wherein: In the mixing and shaking step, the vegetable oil-based epoxy ring-opening monomer, styrene monomer, acrylamide monomer, vinyl acetate monomer, and acrylonitrile monomer are sequentially added dropwise into the aqueous phase solution to obtain the oil-water mixed solution.
6. The method according to claim 1, wherein: In the mixing and shaking step, the oil phase solution comprises: 10 to 40 parts by weight of a vegetable oil-based epoxy ring-opening monomer, 1 to 10 parts by weight of a styrene monomer, 2 to 5 parts by weight of an acrylamide monomer, 3 to 10 parts by weight of a vinyl acetate monomer, and 1 to 8 parts by weight of an acrylonitrile monomer.
7. The method according to claim 1, wherein: In the polymerization step, the time for deoxygenation by nitrogen flow is 0.5 to 1 hr.
8. The method according to claim 1, wherein: In the polymerization step, the Pickering mixed solution includes 50 to 150 parts by weight of the Pickering emulsion and 0.3 to 0.8 parts by weight of the water-soluble initiator.
9. The method according to claim 1, wherein: In the polymerization step, the Pickering mixed solution is polymerized at a temperature of 60 to 80° C. for 3 to 6 hours.
10. The method according to claim 1, wherein: In the polymerization step, the water-soluble initiator includes one or more of ammonium persulfate, potassium persulfate, and metal salts of peroxides.
11. The method according to claim 1, wherein the preparation method of the vegetable oil-based epoxy ring-opening monomer comprises: (S1A) mixing 10 to 40 parts by weight of vegetable oil, 1 to 6 parts by weight of N-methylethanolamine, and 0.1 to 2 parts by weight of a catalyst, sealing and heating to 50 to 80° C., reacting for 8 hours, and then removing unreacted products and the catalyst to obtain a vegetable oil-based precursor; (S2A) mixing 10 to 40 parts by weight of a vegetable oil-based precursor and 4 to 25 parts by weight of an acid anhydride, sealing and heating to 60 to 80° C., reacting for 8 to 12 hours, and removing unreacted products to obtain a vegetable oil-based acrylate monomer; (S3A) mixing 10 to 40 parts by weight of a vegetable oil-based acrylate monomer, 3 to 10 parts by weight of perbenzoic acid, and 5 to 15 parts by weight of sodium carbonate, and stirring the mixture in a sealed container at room temperature for 12 hours, and then removing unreacted products to obtain a vegetable oil-based epoxy monomer; and (S4A) 10 to 40 parts by weight of a vegetable oil-based epoxy monomer and 3 to 10 parts by weight of perchloric acid are mixed, reacted at room temperature for 12 to 24 hours, and then unreacted products are removed to obtain a vegetable oil-based epoxy ring-opening monomer.
12. The method according to claim 1, wherein the method for preparing the aramid fiber suspension comprises: (S1B) dissolving 5 to 30 parts by weight of sodium hydroxide in 100 to 500 parts by weight of deionized water to obtain a sodium hydroxide solution; (S2B) mixing 5 to 30 parts by weight of polyterephthalamide fiber, 1000 to 2000 parts by weight of DMSO, and the sodium hydroxide solution, and stirring the mixture for 6 to 12 hours to obtain a uniform solution; (S3B) subjecting the homogenous solution to high-speed shaking and vacuum filtration to obtain aramid fiber precipitate; (S4B) washing the aramid fiber precipitate with saturated sodium chloride to obtain a purified aramid fiber; and (S5B) The aramid fiber purification product is diluted with deionized water to obtain an aramid fiber suspension.
13. The method according to claim 11, wherein: The vegetable oils and fats include: one or more of sunflower oil, Chinese tallow tree oil, olive oil, linseed oil, rubber seed oil, castor oil, tung oil, and palm oil; or The catalyst comprises: one or more of sodium hydroxide, potassium hydroxide, and sodium methoxide.
14. A polymer composite emulsion prepared by the method according to any one of claims 1 to 13, wherein the polymer composite emulsion comprises polymer composite microspheres, and the polymer composite microspheres comprise: A core, the composition of which includes: polystyrene; A first shell layer is coated on the outer edge of the core, and its composition materials include: polyacrylonitrile; A second shell layer is coated on the outer edge of the first shell layer, and its composition material includes: polyvinyl acetate; A third shell layer is coated on the outer edge of the second shell layer, and its composition materials include: plant oil polymer; and The aramid fiber is arranged on the outer edge of the third shell layer.
15. The polymer composite emulsion according to claim 14, wherein: Based on the total weight of the polymer composite microspheres, the microspheres comprise: A parts by weight of aramid fiber, B parts by weight of vegetable oil polymer, C parts by weight of polyacrylamide, D parts by weight of polyvinyl acetate, E parts by weight of polystyrene, and F parts by weight of polyacrylonitrile, wherein: A is 0.1 to 2, B is 20 to 40, C is 10 to 20, D is 5 to 25, E is 4.9 to 23, F is 5 to 10, and A+B+C+D+E+F=100.
16. A method for preparing a lithium ion battery separator, comprising: Applying the polymer composite emulsion as claimed in any one of claims 13 or 14 to one or both sides of a base film to obtain a composite membrane; and The composite separator is dried at a temperature of 50 to 70° C. for 0.5 to 1 min to obtain the lithium ion battery separator.
Citation Information
Patent Citations
Vegetable fat-based latex, preparation method and application thereof
CN113249074A
Vegetable oil-based polyacrylate nonionic emulsion as well as preparation method and application thereof
CN113307918A